2004
DOI: 10.1158/1078-0432.ccr-03-0535
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics Compete with Dose as Predictors of Acute Treatment Toxicity in Early Phase Clinical Trials

Abstract: Purpose: The purpose of this study was to identify patient characteristics that may be risk factors or markers of susceptibility to adverse treatment effects in cancer Phase I and II clinical trials.Patients and Methods: A total of 459 patients enrolled in 23 therapeutic Phase I and II studies at the Fox Chase Cancer Center were included in the analysis. Patient-specific characteristics, medical and treatment history, doses of experimental agents, and graded toxicities were extracted from case report forms. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 11 publications
0
65
0
Order By: Relevance
“…Elderly cancer patients are a unique population in cancer care, because they are more likely to have metastatic disease and often have more symptoms than younger patients (2)(3)(4). Poor performance status and comorbidities, which are commonly experienced by elderly patients, have been related to negative treatment outcomes in chemotherapy for older adults (3)(4)(5)(6)(7)(8)(9)(10)(11). However, several studies have established chemotherapy as an effective treatment with minimal toxicity in elderly patients on the basis of age alone (4,8,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Elderly cancer patients are a unique population in cancer care, because they are more likely to have metastatic disease and often have more symptoms than younger patients (2)(3)(4). Poor performance status and comorbidities, which are commonly experienced by elderly patients, have been related to negative treatment outcomes in chemotherapy for older adults (3)(4)(5)(6)(7)(8)(9)(10)(11). However, several studies have established chemotherapy as an effective treatment with minimal toxicity in elderly patients on the basis of age alone (4,8,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our study has evaluated multiple molecularly targeted drugs in various tumor types, thus, our results cannot necessarily be applicable to all such agents in a specific way in view of the variety of these agents, their heterogeneous mechanisms of action, and adverse event profiles in different patient populations. Of note, another group examining the effects of patient characteristics on acute treatment toxicity in early phase clinical trials has used a similar methodology (23).…”
Section: Discussionmentioning
confidence: 99%
“…A modified toxicity index (TI) was calculated using the methods of Rogatko et al (23). Depending on the protocol, adverse events were graded on Consortium studies by the National Cancer Institute Common Toxicity Criteria versions 2.0 or 3.0.…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis of multiple phase I and early phase II trials revealed that dose is not always a significant predictor of toxicity (1). Even with conventional patient selection criteria that included the requirement for normal or near-normal hepatic and renal function, patient characteristics had greater predictive value than dose for the toxicity for several agents.…”
mentioning
confidence: 85%